On becoming a consultant: A study exploring the journey to consultant practice. Issue 1 (February 2016) - Henwood, S.; Booth, L.
Abstract: Background: This paper reports a qualitative study exploring the establishment of non-medical consultant roles in Radiography. Given the difficulties reported in recruiting and retaining staff in these posts, we hope this paper offers a historical documentation of those consultants who were some of the first in post, sharing their stories of how they obtained and transitioned into their roles. Methods: This paper is part of a two year case study exploring the leadership domain of consultant practice. The focus of this paper is a reflection, by the consultants, of their journey to becoming a consultant; a documentation of some of the practical issues in establishing the roles; and the transition to higher levels of practice. Eight consultant radiographers participated in the initial interviews (two consultants withdrew from the study subsequent to this). In-depth iterative interviewing was used to explore and record individual stories and experiences. Findings: The consultants shared their perceptions of being in post, including their own motivation to progress to a new role, how prepared they felt initially, the lack of role models, the lack of clarity surrounding the role and a perception of 'being on display'. Conclusions: The paper offers insight into the journey of these consultants and some of the common characteristics they share. These characteristics give some indication of what motivated them to step into higher level roles, in particular the need to drive change and improvement. The paper also offers suggestions for how the transition into the role could be more effectively supported. Highlights: Identifies characteristics thought to contribute to effective consultant practice. A desire to change practice is a major motivator in applying for a consultant post. The consultant role was a natural evolution for some, not a desired career pathway. There is recognition that the initial consultants were pioneers for the profession. Indications of how role transition could have been better supported are outlined.